Enantioselective Organocatalytic Hydride Reduction - Ouellet, Stéphane G; Tuttle, Jamison B; MacMillan, David W. C (Journal of the American Chemical Society, 2005)
The first enantioselective organocatalytic hydride reduction has been accomplished. The use of iminium catalysis has provided a new organocatalytic strategy for the enantioselective reduction of β,β-substituted α,β-unsaturated aldehydes to generate β-stereogenic aldehydes. The use of imidazolidinone 2 as the asymmetric catalyst has been found to mediate the transfer of hydrogen to a large class of enal substrates from ethyl Hantzsch ester. The capacity of catalyst 2 to accelerate E − Z isomerization prior to selective E-olefin reduction allows the implementation of geometrically impure enals in this operationally simple protocol.